The Effects of Exercise on Spleen Fibrosis and Macrophage Number in D-Galactose-Induced Aging Rat Model - Pramita Dwinda Mulyana; Widya Wasityastuti; Fajar Dwi Astarini; Nungki Anggorowati; Nur Arfian (Faculty of Medicine, Universitas Diponegoro, 2022)
Background: Spleen plays a role in human immune system as well as in recycling and filtering blood. The aging spleen is associated with fibrosis and impaired immune system, increasing individual vulnerability to getting infections. Regular physical activity is essential to maintain and enhance body fitness, endurance, and immune system.Objective: This study aimed to investigate the effects of mild and moderate-intensity treadmill exercise on the aging spleen by examining fibrosis and the number of macrophages in d-Galactose-induced aging rat models.Methods: Twenty-four male Wistar rats were randomly divided into four groups: G1 (control group), G2 (d‐Galactose, no exercise), G3 (d‐Galactose, low-intensity exercise), and G4 (d‐Galactose, moderate-intensity exercise). d-Galactose was administered intraperitoneally on day 0 and treadmill exercise was given for four weeks following the modified Brown et al. (2007) protocol. Spleens were histologically processed and stained for picrosirius red and against CD68+ antibody. Percentage of fibrosis fraction area and macrophage cell count were obtained using ImageJ, and the data were analyzed statistically using SPSS software.Results: The aging spleen did not show any differences in weight, length, and width among groups (P > 0.05). The administration of d-Galactose in rats causes fibrosis and an increased number of macrophages. Low and moderate-intensity treadmill exercise could not lower the percentages of fibrosis fraction area. However, the moderate-intensity treadmill exercise was effective in lowering macrophage number.Conclusion: Moderate-intensity treadmill exercise was effective in lowering macrophage cell count in the aging rat spleen induced by d-Galactose.